JUSTIFICATION OF THE FORM OF THE CUTTING EDGE OF THE KNIFE OF THE EXPERIMENTAL WORKING BODY OF THE CULTIVATOR - B.U. Nurabaev; R.T. Tolibaev; N .J. Kilichov (Web of Journals Publishing, 2024)
The satata presents the results of theoretical studies to substantiate the shape of the cutting edge of the knife of the experimental working part of the cultivator. Calculations carried out based on the derived analytical dependencies showed that to ensure the sliding of particles along the cutting edge of the knife, its installation angle should be in the range of 145...1500.
Keywords: Experimental working body of a cultivator, spacing of cotton rows, shape of the cutting edge of the knife, angle of entry of loosening plates into the soil, speed of particle sliding along the cutting edge of the knife.